Multilevel Analysis of Community Health Center, Performance of Health Personnel: Evidence from Ngawi, East Java - Rahayu Zulaikah; Didik Tamtomo; Endang Sutisna Sulaeman (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Quality health services are one of the priorities and development goals in the health sector. Community Health Center as the first-line public services in the health sector are expected to provide quality services for the community. The quality of health services in community health center can be seen from the performance of the health personnel. This study aims to determine the factors that determine the performance of health personnel in health centers.Subjects and Method: This study used an observational analytic method with a cross sectional approach. The study was conducted in 24 community health center in Ngawi, East Java on June-July 2019. The total sample of 216 health personnel of the community health center was selected based on proportional random sampling. The dependent variable of this study was the performance of health personnel. The independent variables in this study were accreditation status, education, income, work length, motivation, satisfaction, and workload. The data collections used questionnaires and were analyzed using multilevel linear regression test with Stata 13.Results: The performance of health personnel significantly improved with good accreditation status (b = 2.87; 95% CI= 0.03 to 5.71; p= 0.048), high education (b= 0.63; 95% CI = 0.13 to 1.13; p= 0.013), and high workload (b= 0.86; 95% CI= 0.34 to 1.39; p= 0.001). There was a contextual effect of the performance health personnel (ICC= 53.69%).Conclusion: Good accreditation status, higher education and high work responsibilities increase the performance of the health personnel. There was a contextual effect of health centers on the health personnel.Keywords: performance of health personnel, community health center, multilevel linear regressionCorrespondence:Rahayu Zulaikah, Ngawi Health Office, Jl. S. Parman 25 A, Ngawi, East Java. Email: dokterrahayu@yahoo.co.id. Mobile phone: 081946059306Journal of Health Policy and Management (2020), 5(1): 13-22https://doi.org/10.26911/thejhpm.2020.05.01.02